(untitled) (Fiep Bulletin - online, 2014)
This study aimed to determine the sampling rate, the filtering cut-off frequency and the number of executions for data collection of dynamic variables in underwater running. A 27-year-old male subject participated of this study (1,80m of height and 84,3kg of body mass. A force plate was placed at the bottom of a thermal swimming pool (30±1°C) between boxes that formed an 8-meter walkway. The force plate was sampled at 1000 points per second. After the anthropometrical measurements, the subject was asked to enter in the pool was instructed to walk over the walkway in two distinct immersion levels: hip and sternum. Data were exported and treated through Scilab (INRIA) software. Data were analyzed through descriptive and inferential statistics. When analyzing the result of spectral density curve (Figure 1), it was observed that data could be collected with a sampling rate of 200 points per second, 10 times higher the signal frequency, which guarantees its integrity during acquisition. These results could also be used to set the filtering cut-off frequency of 20 Hz, once the original signal’s frequency is lower than the cut-off frequency. Results of the accumulated coefficient analysis are presented in Figure 3. It was observed a stabilization of the values of variables starting in the 6th passage in the walkway. In order to guarantee quality of data one suggests collecting 10 valid passages for each subject in situation.